2021
DOI: 10.1016/j.jbc.2021.100371
|View full text |Cite
|
Sign up to set email alerts
|

Multiple variants of the fungal effector AVR-Pik bind the HMA domain of the rice protein OsHIPP19, providing a foundation to engineer plant defense

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 73 publications
(109 citation statements)
references
References 75 publications
2
107
0
Order By: Relevance
“…Studies with the NLR pair Pik from rice have shown that the strength of effector binding to integrated domains in vitro can correlate with immune responses in planta (5254). Of the AvrRps4 mutants we tested to validate the RRS1 WRKY interface, all except N171A and Q194A prevented binding in vitro (by ITC) and in planta (by co-IP), and these did not give cell death in Nicotiana species when co-expressed with either RRS1-R/RPS4 or RRS1-S/RPS4.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with the NLR pair Pik from rice have shown that the strength of effector binding to integrated domains in vitro can correlate with immune responses in planta (5254). Of the AvrRps4 mutants we tested to validate the RRS1 WRKY interface, all except N171A and Q194A prevented binding in vitro (by ITC) and in planta (by co-IP), and these did not give cell death in Nicotiana species when co-expressed with either RRS1-R/RPS4 or RRS1-S/RPS4.…”
Section: Discussionmentioning
confidence: 99%
“…To further demonstrate the flexibility of the pOPIN-GG vectors, we next cloned an interaction partner of AVR-PikF, OsHIPP19 (Maidment et al, 2021), into pPGN-C with a 6xHIS-GB1 tag. We co-transformed E. coli SHuffle cells with the 6xHIS-GB1-OsHIPP19 vector and an untagged variant of AVR-PikF (in pPGC-K), expressed the proteins, and performed Ni 2+ -IMAC coupled with size exclusion chromatography (SEC) to purify a complex between AVR-PikF and OsHIPP19 (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Next, we tested the influence of the key polymorphisms identified in the yeast-two hybrid mutant screen on in vitro sHMA94 binding. We first measured the effect of the Asp to Asn mutation at position 66 in APikL2, as this is the only polymorphism between APikL2A and APikL2F that is predicted to locate to the HMA binding interface (based on [7,10,46]).…”
Section: Asn-66 Facilitates Apikl2 Binding To Shma94mentioning
confidence: 99%
“…The remarkable finding that a single type of NLR-integrated domain mediates perception of three sequence diverse blast fungus effectors indicates that this pathogen has evolved multiple effectors to target HMA-containing proteins. Indeed, two recent studies validated the view that, before being baited by NLR proteins, AVR-Pik and other HMA binding effectors have convergently evolved to target host proteins of the heavy metal-associated plant proteins (HPPs) and heavy metal-associated isoprenylated plant proteins (HIPPs), collectively referred to as small HMA (sHMA) proteins [45][46][47]. sHMA proteins are metallochaperone-like proteins that belong to an expanded family of up to 100 members in a single grass species that contribute to metal homeostasis and detoxification during abiotic stress [45,48].…”
Section: Introductionmentioning
confidence: 96%